Differential gene expression analysis by cDNA-AFLP between flower buds of Phalaenopsis Hsiang Fei cv. H. F. and its somaclonal variant - Hsu, T.; Tsai, W.; Wang, D.; Lin, S.; Hsiao, T.; Chen, W.; Chen, H.
Somaclonal variation occurs during plant tissue culture and introduces changes that can result in the development of desirable traits. Using cDNA-amplified restriction fragment length polymorphism (cDNA-AFLP)analysis, we compared gene expression patterns between flower buds from wild type (donor)plants of Phalaenopsis Hsiang Fei cv. H. F., whose flowers are bronze in color, and from its somaclonal variants, whose flowers have a mosaic yellowish color, and sometimes an aberrant shape. Using 128 fluorescently labeled primer sets, a total of 2269 transcript-derived fragments (TDFs)were analyzed. Among them, 25 TDFs were differentially expressed between the wild type plant and its variant. After cloning and sequencing these differentially expressed TDFs, we found that they contained 27 distinct sequences. Further confirmation of the differential expression of these sequences was carried out by using semi-quantitative RT-PCR. We found that five sequences showed higher expression levels in the wild type plant compared to those in the variant plant. These corresponded to sequences that encoded casein kinase, isocitrate dehydrogenase, cytochrome P450, EMF2, and a no hits found protein. In contrast, two other sequences, whose roles were unknown, were expressed to a higher level in the variant plant compared to those in the wild type plant. The differential expression of these genes may lead to the mosaic color patterns as well as the aberrant flower shapes in the somaclonal variants of Phalaenopsis Hsiang Fei cv. H. F.
Keywords: CDNA-AFLP; PHALAENOPSIS ORCHID; SEMI-QUANTITATIVE RT-PCR; SOMACLONAL VARIANT; TRANSCRIPT-DERIVED FRAGMENT (TDF)